Constructing ecological discourse in online news: A critical ecolinguistic analysis of Detik.com's coverage of the Al-Khoziny Islamic Boarding School collapse - Khusnul Khotimah; Farid Pribadi; Hanif Siswanto (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
This study aims to analyze the construction of ecological discourse in the reporting of the collapse of the Al-Khoziny Islamic Boarding School in Sidoarjo as covered by Detik.com. The study employs a Critical Eco-Discourse Analysis approach, combining Stibbe’s ecolinguistic framework and Fairclough’s critical discourse model, to examine how events, actors, and ecological ideologies are represented in online news texts. Data were collected from Detik.com articles reporting the chronology, causes, and impacts of the building collapse. The findings indicate that the media primarily framed the incident as a technical tragedy while largely overlooking ecological and regulatory factors such as dense spatial planning, soil conditions, and limited building standards. The role of supervisory institutions and eco-boarding school mitigation practices was rarely mentioned. These results highlight the need to strengthen ecological discourse in pesantren reporting by involving diverse sources and emphasizing environmental, governance, and student safety aspects. This study concludes that Detik.com’s coverage tends to marginalize ecological dimensions and institutional responsibility, thereby limiting public understanding of the structural and environmental factors underlying the incident. The study contributes theoretically to the ecolinguistics of pesantren and practically to the development of safer and more sustainable pesantren management policies.